2016
DOI: 10.4102/rw.v7i1.85
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of a reading project in the Northern Cape, South Africa

Abstract: The topic of this longitudinal study was reading promotion and its perceived benefits. The aim was to determine if reading promotion can lead to reader development and if reader development can lead to self-development, as is often claimed in the literature. A reading promotion project in the Northern Cape, South Africa, was monitored over a period of five years by using a selection of qualitative and quantitative data collection methods. The outcome of the study indicates that the reading promotion project wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Generally, sustaining funded reading programmes has not been successful in most cases, due to running out of funds, little or no evaluation of the programme, or lack of a plan for sustainability (Snyman, 2016). In the case of this study, as the ERP was part of my defined research period, I had to consider ways that would sustain the reading intervention.…”
Section: Sustainability Of the Extensive Reading Programmementioning
confidence: 99%
“…Generally, sustaining funded reading programmes has not been successful in most cases, due to running out of funds, little or no evaluation of the programme, or lack of a plan for sustainability (Snyman, 2016). In the case of this study, as the ERP was part of my defined research period, I had to consider ways that would sustain the reading intervention.…”
Section: Sustainability Of the Extensive Reading Programmementioning
confidence: 99%
“…Teacher participants urged ESL teachers to encourage learners to read silently, as this would help learners to develop the strategies needed for reading fast with better comprehension. Reading aloud, on the other hand, helps learners acquire language skills (Snyman, 2016). Most ESL teachers indicated that reading aloud developed word-sound awareness.…”
Section: Leaners' Reading Experiencementioning
confidence: 99%
“…From parents' responses it is evident that the EL2 learners received less frequent exposure to book reading than in the case of EL1 learners. Reduced exposure to books reduces opportunities to engage phoneme-grapheme coupling skills and may extenuate reliance on print as opposed to decontextualised language and word play for literacy (Goldstein et al 2017:99;Snyman 2016:8 Willenberg 2007. Limited literacy experience therefore may contribute to the lower decoding skills and overall poorer phonemic awareness skills of the EL2 learners.…”
Section: Decodingmentioning
confidence: 99%